Напрями забезпечення інтересів працівників при реорганізації підприємств - Маісурадзе, М.Ю. (Стратегія і механізми регулювання промислового розвитку, 2013)
Досліджено проблемні питання, присвячені забезпеченню інтересів працівників при реорганізації підприємств. Проведено аналіз визначень категорії «інтересу» та «охоронюваного законом інтересу» відповідно до норм чинного законодавства на основі досліджень останніх розробок із цієї проблеми. Визначено, що інтерес є прагненням або причиною дій, отже, він не має законодавчого чи нормативного закріплення, що спричиняє ускладнення при його забезпеченні. Встановлено, що інтереси працівників мають бути чітко визначені у законодавчому чи нормативному акті або у трудовому договорі для того, щоб їх забезпечення та реалізація при реорганізації підприємства відбувалися безперешкодно й охоронялися законом. Исследованы проблемные вопросы, посвященные обеспечению интересов работников при реорганизации предприятий. Проведен анализ определений категории «интереса» и«охраняемого законом интереса» в соответствии с нормами действующего законодательства на основе исследований последних разработок по этой проблеме. Определено, что интерес является стремлением или причиной действий, следовательно, он не имеет законодательного или нормативного закрепления, что вызывает осложнение при его обеспечении. Установлено, что интересы работников должны быть четко определены в законодательном или нормативном акте или в трудовом договоре для того, чтобы их обеспечение и реализация происходили беспрепятственно и охранялись законом. The problematic issues devoted to the employees’ interests assurance during the reorganization of enterprises are studied. The definitions of such categories as “interest” and “interest protected by the law” in accordance with the national legislation and on the basis of the latest research on this issue are analyzed. It is established that the national legislation does not contain the term “interest” of the employee. At the same time, the rights and duties of the labor relations’ participants can be defined not only in the laws and regulations, but also in the local laws and individual employment contracts. It was determined that the representatives of the employees’ interests play an important role in assurance of their rights through the labor unions or associations of employees. It was established that the interest is a desire or cause of action. Therefore, it has no legislative or regulatory fix that causes complications for its assurance. The optimal combination of the interests of employeesand employers is possible through the implementation of existing labor legislation grounded on the principles of the labor law, for example, as socio-economic partnership. It was determined that the current labor legislation lets the termination of the employment contract by the owner’s initiative or by its authorized person. In addition, during the reorganization the employment relationship with the employee must continue, but it does not oblige the employer to make a new contract, and, at the same time, all the conditions established by the preliminary contract must be fully applied. The situation with employees during the reorganization becomes more complicates because of the lack of regulations establishing the responsibilities of new owners of an enterprise (that is set up) to hire workers who have worked in the structure of the previous one attached to another entity or detached as a result of the reorganization into several independent enterprises. Thereby the employees’ interests must be clearly defined by the law or regulation, or by the employment contract in order to assure their implementation free and under the law.